ANALISIS HARGA SAHAM PT. BANK SAUDARA Tbk. PASCA ESOP DAN MSOP TAHUN 2010 - , Muhammad Adlan, S.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This research aim to estimate an intrinsic value of Bank Saudara share after ESOP & MSOP Program by using discounted cash flow method and relative valuation. This research also used data of Bank Saudara financial statementâs during the last six year from 2005 until 2010. Analysis of discounted cash flow conducted by: sales or earnings projection analysis, financial statement projection, free cash flow projection, discount rate determination and terminal value and value estimation. Relative valuation started with searching similar company in the same field of industry and chosening and specifying appropriate ratio or multiples from similar company. This Multiples used to convert a relevant book value variable from Bank Saudara become an estimation of market value. Multiples or ratio which used were: PER (Price Earning Ratio), and PBV (Price to Book Value). The result from this research by using discounted cash flow method obtained an intrinsic value estimation of Bank Saudara share per December 2010 range from Rp338,34 up to Rp341,65. Result by using relative valuation obtained the following result: for the estimation of stocks price per share Bank Saudara by using PER equal to Rp371,- using PBV ratio equal to Rp147,-. The mean from both method equal to Rp258,73. Based on this both approaching, price of Bank Saudara share at this time possibility of undervalued.